Manfaat NMES dan Terapi Latihan untuk Kekuatan Quadriceps, LGS dan Fungsional Lutut Pasien Post TKR - Success, Tazkiyatun Nisa Attaufiq Lulu Desara; Wijaya, Ezra Bernadus; Boroh, Zeth (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Postoperative Total Knee Replacement (TKR) patients often face various clinical problems, including quadriceps muscle weakness, limited range of motion of the knee joint, swelling, and pain that can have a significant impact on functional movement ability, independence of daily activities, and overall quality of life. The condition demands the role of the physiotherapist in providing appropriate and comprehensive interventions to facilitate the patient's recovery. One approach that can be done is to provide a combination of Neuromuscular Electrical Stimulation (NMES) modalities and exercise therapy. This study aims to evaluate the benefits of NMES and exercise therapy combination interventions in improving quadriceps muscle strength, knee joint range of motion, and functional mobility ability in post-TKR patients. The research design used a case study method involving three patients who were in phase 2 (motion phase), namely 3 days to 6 weeks after TKR surgery. Patients show complaints in the form of weakness of the quadriceps muscles, limited range of joint movement, and decreased knee function function. Physiotherapy interventions were given as many as 8 meeting sessions with a frequency of 2 times a week. The intervention program consisted of administering NMES to the quadriceps muscle and functional exercises such as sit to stand exercise, gait training, strengthening exercises using resistance bands in the ankle joint, and stair climbing. The results showed a significant increase in quadriceps muscle strength, an increase in the range of motion of the knee joint, and an improvement in functional movement ability after all intervention sessions were completed. These findings confirm that the combination of NMES with exercise therapy can be an effective rehabilitation strategy for post-TKR patients. The implementation of this method has the potential to speed up recovery, reduce dependence on others, and improve the patient's quality of life in a sustainable manner.